THE CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING ABILITY IN DESCRIPTIVE TEXT OF THE TENTH-GRADE STUDENTS OF SMAN 1 MENGWI IN ACADEMIC YEAR 2022/2023 - Danik Eka Pradana; Putu Ayu Paramita Dharmayanti; Anak Agung Putu Arsana (Academic Journal on English Studies (AJOES), 2023)
The study aimed at figuring out the correlation between grammar mastery and writing ability in descriptive text of the tenth-grade students of SMA N 1 Mengwi in academic year 2022/2023. The design was correlation research design. Two research instruments are used by the researcher; there are simple present test for grammar mastery and descriptive text for writing ability. There were 43 subjects who consist of 19 males and 24 females and they were determined by random sampling technique. The result of the test showed that there was significant correlation between grammar mastery and writing ability in descriptive text. The researcher used SPSS 25 as a statistical computation. The result of normality test for grammar mastery was 0.053 and for speaking ability was 0.065; homogeneity test was 0.067; Pearson product moment was 0,000; and for the T-test was 0.001. It indicated that there was a significant correlation between grammar mastery and writing ability in descriptive text. Thus, the hypothesis was significantly accepted. It can be concluded that there was significant correlation between grammar mastery and writing ability in descriptive text of the tenth-grade students of SMA N 1 Mengwi in academic year 2022/2023.